1982
DOI: 10.1104/pp.70.6.1767
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Oat Globulin Precursors

Abstract: The oat (Avena sativa L.) seed globulin was found to be synthesized in vitro as 60,000 to 64,000 dalton precursors. In vivo protein labeling yielded polypeptides of 58,000 to 62,000 daltons, suggesting cleavage of signal sequences from the precursors. Further cleavage is apparently required to separate the a and ,t polypeptide sequences which are known to form disulfide-linked 53,000 to 58,000 dalton species in the (af)6 holoprotein.The data are discussed with respect to analogous synthesis and processing of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
21
0

Year Published

1983
1983
1999
1999

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 11 publications
3
21
0
Order By: Relevance
“…protein synthesis studies (4,12,23,26). Our present results from the in vivo labeling study of total globulin in developing oat groats support the previous observations.…”
Section: Adeli and Altosaarsupporting
confidence: 81%
See 3 more Smart Citations
“…protein synthesis studies (4,12,23,26). Our present results from the in vivo labeling study of total globulin in developing oat groats support the previous observations.…”
Section: Adeli and Altosaarsupporting
confidence: 81%
“…Brinegar and Peterson (4) have recently reported similar observations. They suggested that the 58 to 62 kD polypeptides are the precursors of a anda globulin species with mol wt 38 kD and 21kD.…”
Section: Adeli and Altosaarsupporting
confidence: 67%
See 2 more Smart Citations
“…2a). Legumin in legumes (Croy et al, 1980;Spencer & Higgins, 1980;Barton et al, 1982), and leguminlike storage proteins in oats (Avena) (Brinegar & Peterson, 1982) and rice (Oryza) (Yamagata et al, 1982) are also synthesized from precursors in which the a-and fl-subunits are peptide-bonded.…”
mentioning
confidence: 99%